Ultrastable Organic Anode Enabled by Electrochemically Active MXene Binder toward Advanced Potassium Ion Storage - Zhou, Shujie; Zhang, Peng; Li, Yanze; Feng, Lingfei; Xu, Mengyao; Soomro, Razium A; Xu, Bin (ACS nano, 2024)
Conjugated carbonyl compounds are regarded as promising organic anode materials for potassium ion batteries (PIBs) due to their rich redox sites, excellent reversibility, and structural tunability, but their low electrical conductivity and severe solubility in organic electrolytes have substantially restricted their practical application. Herein, 2D MXene is utilized as an electrochemically active binder to fabricate perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) electrodes for high-performance PIBs. MXene, coupled with Super-P particles, served as a binder and conductive matrix to facilitate rapid ion and electron transport, restrain the solubility of PTCDA, promote potassium adsorption, and alleviate the volume expansion of PTCDA during potassiation. Consequently, the PTCDA electrode bonded by the MXene/Super-P system delivers excellent potassium storage performance in terms of a high capacity of 462 mAh g–1 at 50 mA g–1, superior rate capability of 116.3 mAh g–1 at 2000 mA g–1, and stable cycle performance over 3000 cycles with a low capacity decay rate of ∼0.0033% per cycle. When configured with the PTCDA@450 cathode, an all-PTCDA potassium ion full cell delivers a maximum energy density of 179.5 Wh kg–1, indicating the superiority of MXene as an electrochemically active binder to promote the practical application of organic anodes for PIBs.